A review of Robert Broom’s therapsid holotypes: have they survived the test of time? - Wyllie, Alistair (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 2003)
While still a medical student in Scotland in the late 1880s, Robert Broom had already identified the principal aim of his scientific career as being ‘to solve the problem of the origin of the mammals’. In Australia, between 1892 and 1896, his work on extant and fossil marsupials and monotremes established that, contrary to the then prevailing scientific opinion which supported a polyphyletic origin for mammals from a diverse range of amphibians and reptiles, the most important living class had been monophyletically derived, most likely from a lineage of Karoo therapsid reptiles. Later, on a trip to the United States in 1909/10 he revived the theory which proposed the existence of a close relationship between the South African therapsids and the Permian ‘pelycosaur’ reptiles of North America. The third, and most extensive element of Broom’s task was carried out almost exclusively in South Africa over a period spanning more than half a century during which he created 369 therapsid holotypes, 168 of which were allocated to new genera. This paper establishes that of those holotypes, approximately 57% currently remain valid according to the parameters defined herein. While such a figure may initially seem to support Broom’s reputation as an ‘arch splitter’, it may equally be reflective of the fragmentary state of therapsid systematics at the time when Broom carried out the majority of his research. Today, Broom is most widely-remembered for the celebrated series of fossil hominid discoveries which he made towards the end of his life in the limestone caves of the Transvaal. However, because the task of unravelling the story of the evolution of the mammals was the one which first motivated his interest in science and which formed the single continuous thread running throughout a long and otherwise varied career, it is perhaps still more accurate to view Broom principally as one of the great Karoo (and, in particular, therapsid) palaeontologists.